Zur Systematik der Gattung Holcogaster Fieb. (Heteroptera: Pentatomidae). - Wagner, Eduard (Contributions to Entomology = Beiträge zur Entomologie, 1955)
Nomenclatural Actslongicornis Wagner, 1955 (Holcogaster), spec. n.exilis (var.) Horvath, 1903 (Holcogaster fibulata), stat. n. now sspec. of Holcogaster fibulata Horvath, 1903